2021
DOI: 10.1111/wrr.12958
|View full text |Cite
|
Sign up to set email alerts
|

Bromelain‐based enzymatic debridement of chronic wounds: Results of a multicentre randomized controlled trial

Abstract: Chronic wounds are estimated to affect over 6 million people annually in the United States with an estimated annual cost of $25 billion. Debridement represents a key step in their management and is considered a basic necessity to induce the functional process of tissue repair. However, there is an unmet need for an efficient rapid acting non-surgical debridement agent. Bromelain-based enzymatic debridement has been proven to provide an effective, selective and safe non-surgical debridement in deep burns. Escha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
0
4
0
2
Order By: Relevance
“…They found faster healing with ESX (55.1% vs. 29.2% gel group) and complete debridement with 10 daily treatments (7.6 ± 4.1 ESX vs. 8.4 ± 4.1 days gel group). There were no significant safety issues and ESX demonstrated a favourable benefit to risk profile in 6 months follow‐up 49 …”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…They found faster healing with ESX (55.1% vs. 29.2% gel group) and complete debridement with 10 daily treatments (7.6 ± 4.1 ESX vs. 8.4 ± 4.1 days gel group). There were no significant safety issues and ESX demonstrated a favourable benefit to risk profile in 6 months follow‐up 49 …”
Section: Discussionmentioning
confidence: 92%
“…There were no significant safety issues and ESX demonstrated a favourable benefit to risk profile in 6 months follow-up. 49 Schulz et al performed a clinical trial including 26 patients with deep facial burns, where they found significantly superior functional and cosmetic outcomes from NXB compared to surgical debridement (SD) based on a series of objective readings, e.g., exameter ® MX 180 that measures scar erythema and melanin, and Patient and Observer Scar Assessment Scale (POSAS). 50 Rosenberg et al (2014) reported promising results from BBD in a multicenter RCT (NCT #: NCT00324311) with 182 patients.…”
Section: Safety Profilementioning
confidence: 99%
“…Os componentes naturais desses tratamentos não cirúrgicos são adequados para a cicatrização de feridas [6]. De fato, um estudo de controle randomizado demonstrou que o mel pode ser usado como um agente de desbridamento não cirúrgico para feridas crônicas [7].…”
Section: Quais São Os Riscos Potenciais E Complicações Associadas a E...unclassified
“…Wörtlich wird als Proteolyse der Abbau von Eiweiß bezeichnet. Für die Wundbehandlung werden beispielsweise Produkte mit Bromelain, Kollagenase oder Streptokinase und Streptodornase genutzt [ 22 , 26 ]. Auch das proteolytische Débridement ist eher schmerzlos, einfach und sicher durchzuführen.…”
Section: Débridementunclassified